Modelagem hidrológica e hidráulica no rio Maranguapinho mediante cenário de mudanças climáticas - Giordani, Lídio Campos (2018)
The present work presents hydrological and hydraulic modeling in the Maranguapinho River, located in the metropolitan region of Fortaleza. New rain equations were calculated, calculated for the climate change scenarios RCP 4,5 and RCP 8.5, according to the global circulation model CESM1-CAM5. The hydrological modeling was done using the HEC-HMS software, and the SCS-CN methods were used to calculate the effective precipitation, the SCS Unit Hydrographic method, for the hydrographic project generation, and the Muskingum-Cunge method for the propagation of the flood wave in the river. In addition, the dredge of the dredged river and the presence of the Maracanaú dam were considered, based on data from subsequent studies conducted by FUNASA. After determining the flow values ​​for the pre-established scenarios, the HEC-RAS software was used to calculate the height of the river water table and the consequent flood range for three situations: the initial one, considering the data at the time of the execution of the dredging project, with return period of 20 years; the first for the RCP scenario 4.5, with a return period of 50 years; and the second for RCP scenario 4.5, with a 100-year payback period. It was possible to notice a great increase of the flood ranges for the situations that consider changes in the climate (about 11 and 13 times, respectively, compared to the initial situation), generating a greater perception of the importance of research in the theme of climate change which aim to increase the amount of environmental policies that delay human impacts.